Level of the first day underpricing of venture capital backed IPO for the CEE Region in 2000-2012 - Zasępa, Piotr (Analiza niedoszacowania transakcji IPO spółek zasilanych funduszami venture capital w Europie Środkowej i Wschodniej w latach 2000-2012, 2016)
Financial systems in post-communist countries have been developing for almost three decades since market transformation. In 2004 and later in 2007, ten Central and Eastern European states became members of European Union, and in the majority of them capital markets were created. There have been numerous studies which have examined the development of capital markets, however investigations concerning the development of stock exchanges are not so frequent. The aim of the paper is to analyze the underpricing of VC backed Initial Public Offerings carried out on the exchanges in Warsaw, Prague, Vienna, Bratislava and Lubljana in 2000-2012
Nauki o Finansach = Financial Sciences, 2016, Nr 4 (29), s. 64-71
Keywords: VC; backed IPO; IPO; venture capital